What Are the Best Biocompatible Materials for Extracorporeal Membrane Oxygenation - Junya Hagiwara; Jeffrey D. DellaVolpe; Yuichi Matsuzaki (Journal of Functional Biomaterials, 2025)
Extracorporeal membrane oxygenation (ECMO) is a crucial life support therapy for patients with severe cardiac and respiratory failure. However, the complications associated with venoarterial ECMO (VA-ECMO), including thrombus formation, bleeding, and hemolysis, remain significant challenges that impact patient outcomes and healthcare costs. These complications primarily arise from blood–material interactions within the ECMO circuit, necessitating the development of biocompatible materials to optimize hemocompatibility. This review provides an updated overview of the latest advancements in VA-ECMO materials, focusing on cannula, oxygenators, and centrifugal pumps. Various surface modifications, such as heparin coatings, nitric oxide-releasing polymers, phosphorylcholine (PC)-based coatings, and emerging omniphobic surfaces, have been explored to mitigate thrombosis and bleeding risks. Additionally, novel oxygenator membrane technologies, including zwitterionic polymers and endothelial-mimicking coatings, offer promising strategies to enhance biocompatibility and reduce inflammatory responses. In centrifugal pumps, magnetic levitation systems and hybrid polymer-composite impellers have been introduced to minimize shear stress and thrombogenicity. Despite these advancements, no single material has fully addressed all complications, and further research is needed to refine surface engineering strategies. This review highlights the current progress in ECMO biomaterials and discusses future directions in developing more effective and durable solutions to improve patient safety and clinical outcomes.